The Attitude-Behavior Gap – Drivers and Barriers of Sustainable Consumption - Bea Alexandra Wintschnig (Junior Management Science (JUMS), 2021)
Individuals' consumption behavior plays a key role on the path to a sustainable future. Understanding what influences the decision to act in a sustainable manner is therefore crucial. The aim of this thesis is to provide a structured overview of the current state of academic literature on the drivers and barriers of sustainable consumption and to discuss the related phenomenon of the attitude-behavior gap. The identified influencing factors can be broadly divided into two categories: individual-related determinants and environmental determinants. The former includes socio-demographics, personal characteristics and value orientation, non-cognitive factors (habits and emotions) and cognitive factors like knowledge. The environmental determinants comprise product-, service-, or behavior-related factors (such as stereotypes towards sustainable products), corporate activities (e.g., communication efforts), social influence as well as structural conditions like the available infrastructure. From the diversity of influencing factors and their interplay, it becomes clear that to promote sustainable behavior or to close the attitude-behavior gap, a holistic approach is needed that combines different instruments and is adapted to the specific type of consumer behavior.
Keywords: 650; Sustainable consumption; attitude-behavior gap; sustainable choices; sustainable consumer behavior